8m-29=-22+7m

Simple and best practice solution for 8m-29=-22+7m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8m-29=-22+7m equation:


Simplifying
8m + -29 = -22 + 7m

Reorder the terms:
-29 + 8m = -22 + 7m

Solving
-29 + 8m = -22 + 7m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-7m' to each side of the equation.
-29 + 8m + -7m = -22 + 7m + -7m

Combine like terms: 8m + -7m = 1m
-29 + 1m = -22 + 7m + -7m

Combine like terms: 7m + -7m = 0
-29 + 1m = -22 + 0
-29 + 1m = -22

Add '29' to each side of the equation.
-29 + 29 + 1m = -22 + 29

Combine like terms: -29 + 29 = 0
0 + 1m = -22 + 29
1m = -22 + 29

Combine like terms: -22 + 29 = 7
1m = 7

Divide each side by '1'.
m = 7

Simplifying
m = 7

See similar equations:

| 13.7b-6.5=23b+8.3 | | 5n-25=-13+3n | | -7.64+10000= | | y=-3*1+2 | | y=-3*-2 | | 0.6(y+1.5)=-2.1(y-3) | | 6(3+3x)-2=106 | | -2/5(n-1/8)=1/2(n-1/6) | | 10-2m=3m+25 | | 1729x-258=433x-474 | | (2/x^2+12x+36)+(5/x^2+x-30) | | X^2+10x+9=(x+1)(ax+b) | | -2(x-3)+4(2-x)= | | -5y-8=-7y-16 | | 19x-11-17x+14=2x+3 | | [5x-7]=33 | | 8-[(-3+7)-(3-9)]= | | 5+4x-7=4x-2 | | -10-(-3)= | | 0-8y=5 | | -4.07+2.3= | | T=C(2+AB) | | 5(2y+2)-(y+3)= | | abs(3x-4)= | | 1/3t-4/3=5/4t-3/2 | | 3(2x-1)-2(x-4)= | | 8m-5=6m-8 | | (5x-4)(4x+9)=0 | | 4(x+5)+3(x-6)= | | -136-10x=43-17x | | 45x^5+60x^2+15x= | | -2r+3=6-1/2r |

Equations solver categories